(untitled) - Hibbert, Christopher (London, 1979)
Contents: At its height Renaissance Florence was a centre of wealth, power and influence. A republican city-state funded by trade and banking, its bloody political scene was dominated by mercantile families, the most famous of which were the Medici. This book charts the family's huge influence on the political, economic and cultural history of Florence
Keywords: Thành phố Florence, nươc Ý,Florence (Italy); Lịch sử,History; 1421-1737.,1421-1737.